Existence of Nontrivial Solutions for a Critical Perturbed Quasilinear Elliptic System. (17th November 2014) - Zhang, Huixing; Zhang, Xiangzhi
Abstract : We consider a perturbed quasilinear elliptic system involving thep -Laplacian with critical growth terms inR N . Under proper conditions, we establish the existence of nontrivial solutions by using the variational methods.